2021
DOI: 10.2147/ijgm.s326023
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Diffusion Tensor Imaging for Preclinical Therapeutic Efficacy of Umbilical Cord Mesenchymal Stem Cell Transplantation in the Treatment of Spinal Cord Injury

Abstract: Objective In this study, umbilical cord mesenchymal stem cell (UC-MSC) transplantation was used to treat patients with spinal cord injury (SCI). The microstructural changes of the spinal cord before and after transplantation were observed by diffusion tensor imaging (DTI). Methods From January 2014 to May 2015, seven patients who met the inclusion criteria were enrolled in this study. In the experimental group, both UC-MSC transplantation and comprehensive rehabilitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…420,421 Combined transplantation of different types of cells, transplantation of MSCs combined with biomaterials, and comprehensive rehabilitation may be strategies to improve the effect of MSCs in clinical trials. [422][423][424][425] A phase 1/2 clinical trial of cell transplantation combining human autologous Schwann cells and BMSCs was carried out in subacute complete SCI patients and revealed statistically significant improvements in sensory and neurological functions (Table 3). 422 Bone marrow mononuclear cells (BMMCs) and umbilical cord blood-derived mononuclear cells (UCB-MNCs) are both useful cell types for repairing SCI, and their function has been verified in clinical research on SCI (Table 3).…”
Section: Advanced Technology In Clinical Trialsmentioning
confidence: 99%
“…420,421 Combined transplantation of different types of cells, transplantation of MSCs combined with biomaterials, and comprehensive rehabilitation may be strategies to improve the effect of MSCs in clinical trials. [422][423][424][425] A phase 1/2 clinical trial of cell transplantation combining human autologous Schwann cells and BMSCs was carried out in subacute complete SCI patients and revealed statistically significant improvements in sensory and neurological functions (Table 3). 422 Bone marrow mononuclear cells (BMMCs) and umbilical cord blood-derived mononuclear cells (UCB-MNCs) are both useful cell types for repairing SCI, and their function has been verified in clinical research on SCI (Table 3).…”
Section: Advanced Technology In Clinical Trialsmentioning
confidence: 99%
“…The follow-up period ranged from 6 to 60 months. The basic information of the included studies is shown in Additional file 1 : Table S2 [ 23 84 ].…”
Section: Resultsmentioning
confidence: 99%